Impact of FDA black box warning on fluoroquinolone and alternative antibiotic use in southeastern US hospitals. (2nd September 2019) - Yarrington, Michael E.; Anderson, Deverick J.; Dodds Ashley, Elizabeth; Jones, Travis; Davis, Angelina; Johnson, Melissa; Lokhnygina, Yuliya; Sexton, Daniel J.; Moehring, Rebekah W.
Abstract: We analyzed antibiotic use data from 29 southeastern US hospitals over a 5-year period to determine changes in antibiotic use after the fluoroquinolone US Food and Drug Administration (FDA) advisory update in 2016. Fluoroquinolone use declined both before and after the FDA announcement, and the use of select, alternative antibiotics increased after the announcement. Fluoroquinolones are among the 4 most commonly prescribed antibiotic classes. 1, 2 Postmarketing reports of serious adverse events linked to fluoroquinolones include tendonitis, neuropathy, hypoglycemia, psychiatric side effects, and possible aortic vessel rupture, leading to safety label changes in July 2008 and August 2013. 3 In July 2016, the US Food and Drug Administration (FDA) strengthened the "black box" warning following an initial safety announcement in May 2016, recommending avoidance of fluoroquinolones for uncomplicated infections such as acute exacerbation of chronic bronchitis, uncomplicated urinary tract infections, and acute bacterial sinusitis. 4 Concerns over safety and the association with Clostridiodes difficile infection have led inpatient antimicrobial stewardship programs (ASPs) to develop initiatives to promote avoidance of quinolones. The objective of this study was to quantify the effect of the 2016 FDA "black box" update on inpatient antibiotic use among a cohort of southeastern US hospitals.